2021
DOI: 10.2113/2021/3343655
|View full text |Cite
|
Sign up to set email alerts
|

Eocene–Oligocene Crustal Thickening-Collapse of the Eastern Tibetan Plateau: Evidence from the Potassic Granitoids in SW China

Abstract: The eastern Tibetan Plateau is a key part of the eastern India–Asia collisional zone, a region that records multiple overprinting tectonic and magmatic events. This study presents new geochronological, geochemical, and Sr–Nd–Hf–O isotopic data for Cenozoic potassic granitoids in eastern Tibet, southwestern China, which recorded the tectonic evolution of the eastern Tibetan Plateau. These potassic granitoids are formed between 37.6 and 32.9 Ma and are geochemically subdivided into the following: Group 1, adakit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 118 publications
(193 reference statements)
0
1
0
Order By: Relevance
“…The formation of the protolith of our D 1 gneiss fabrics, which formed under granulite facies prior to 32 Ma, can be linked to crustal thinning due to back arc extension and subduction of Neotethys as the SCS opened (e.g., Karig, 1971;Mai et al, 2018). These granulite facies metamorphism and wide-spread regional leucogranitic magmatism played a critical role in crustal weakening before the strike-slip movement (e.g., Chung et al, 1997;Junlai et al, 2020;Gou et al, 2021;Li et al, 2021). As the SCS further rifted, the continental crust was further thinned.…”
Section: Tectonic Implications Of the Evolution Of The Dncv Metamorph...mentioning
confidence: 89%
See 3 more Smart Citations
“…The formation of the protolith of our D 1 gneiss fabrics, which formed under granulite facies prior to 32 Ma, can be linked to crustal thinning due to back arc extension and subduction of Neotethys as the SCS opened (e.g., Karig, 1971;Mai et al, 2018). These granulite facies metamorphism and wide-spread regional leucogranitic magmatism played a critical role in crustal weakening before the strike-slip movement (e.g., Chung et al, 1997;Junlai et al, 2020;Gou et al, 2021;Li et al, 2021). As the SCS further rifted, the continental crust was further thinned.…”
Section: Tectonic Implications Of the Evolution Of The Dncv Metamorph...mentioning
confidence: 89%
“…On the contrary, these magmatism events corresponded to our D 1 granulite facies metamorphism as the thickened crust started to stretch and extend. Geochemical data of Chung et al (1997) and Gou et al (2021) revealed these magmas originated from collapsing of the thickened crust within plate following the India-Eurasia collision. However, the proposed transtension shearing was not the forming mechanism for our D 3 event as a transtensional basin rather than a dome would have been expected in such a case.…”
Section: Figurementioning
confidence: 96%
See 2 more Smart Citations
“…A regional NE–SW compression and crustal thickening event (D1) prior to sinistral shear is also evidenced by: (a) granitic mylonite adjacent to both the ALS and the Red River fault shows early Eocene mica or amphibole Ar/Ar cooling ages (Zhang et al., 2006, Figure 2d); (b) the Ludian‐Zhonghejiang fold‐and‐thrust system, which lies parallel and is situated close to the ARSZ, was active during the period 50‐39 Ma (Cao et al., 2020); (c) a thin‐skinned fold‐thrust stratigraphic succession and the unconformity exists between Paleocene and Lower Eocene strata (45 ± 5 Ma) in Indochina (Liang et al., 2022; Wang & Burchfiel, 1997); (d) Mesozoic granitic and sedimentary rocks situated on the interior of the ARSZ and its flanks record Eocene zircon/apatite fission track and (U–Th)/He ages (Liu‐Zeng et al., 2018; Wang et al., 2020); (e) gneissose folding with sillimanite‐ and garnet‐bearing fabrics that formed due to pure shear deformation in the ARSZ, and which were pervasively developed prior to left‐lateral shearing initiation (Jolivet et al., 2001; Liu et al., 2012; Zhang et al., 2014, 2017a, 2017b); (f) the chronostratigraphic age of formation of the Jianchuan and Lühe syncontractional basins (Eocene: 37–35 Ma), which are interpreted to document synchronous E–W shortening of the ARSZ (Gourbet et al., 2017; Li et al., 2020); and (g) Eocene‐Oligocene potassic granitoids are interpreted as having formed in response to crustal thickening and collapse in the southeastern Tibetan Plateau (Gou et al., 2021). These lines of evidence lead us to propose that micaschists on the southwest side of the ALS massif recorded an episode of crustal stacking above the brittle‐ductile transition zone (∼25 km) during the soft collision stage between the Indian plate and the Eurasian plate (Lee & Lawver, 1995).…”
Section: Discussionmentioning
confidence: 99%